Tanggungjawab Dokter Terhadap Pasien dalam Perjanjian Terapeutik - Komang Ayu Windy Widyastari Putri; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Analogi Hukum, 2020)
Abstract—Humans are living being who have the right to get a good and healthy environment and are entitled to health services. According to article number 36, 2009 about Health, Therapeutic Agreement which is the relationship between doctor and the patient that allow doctor to conduct giving healthcare to the patients according their skills. The background of this paper is because there is an agreement of therapeutic between doctor and patient. The problem rise: 1. what is the law regulation of Therapeutic agreement between doctor and the patient in medical services? 2. How is the civil law and criminal law responsibility between doctor and the patient in therapeutic agreement? This paper is also intended to know about doctor’s responsibility to the patient of therapeutic agreement. Normatic law scientific method is used in writing this paper with statute approach, conceptual approach, and document approach. The source of law study primary secondary, secondary and tarsiers. The conclusion is the terapeutik agreement between doctor and patient is listed under the article of doctor’s responsibility of therapeutical agreement in general can be divided into 3, (1) the act of law violation (Article 1365 Civil Code); (2) irresponsible or careless act (Article 1366 Civil Code); (3) The Responsibility of the Leader to their Ordinate (Article 1367 Civil Code). And added with number.36 Act of 2009 on health, article 56 paragraphs 1, 2, 3, article 57 paragraph 1, 2, article 58 paragraphs 1, 2, 3.